KOMODIFIKASI (KOMODITIFIKASI) DALAM INDUSTRI PERHOTELAN DI BALI - Ratna Sari, Ni Putu (Jurnal Analisis Pariwisata; Vol 16 No 1 (2016): Jurnal Analisis Pariwisata (Juli 2016), 2016)
Comodi cation or comoditi cation has occured in tourism industry, but unfortunately scienti c information on it, especially in the hotel sector is very limited. Thus, cunducting research on such issue and write down the article on the issue has been encouraged, especially on comoditi cation in hotel industries in Bali. The reserach was undertaken in some hotels in Bali. Data were collected through eld observation, conducting interview, and checking documnets (literature review). Data were analysed in a descriptive qualitative analysis. Results of this research showed that there were some forms of comodi cation or comoditi cation observed in hotel sectors in Bali such as on building the temple in the hotel, the use of top of building as a restaurant, placement of solar cell on the top- ated roof of buildings, the placement of Boma carving on “madya mandala” of hotel, klumpu or jineng which was modi ed into resting room, the use of modi ed “canang” as decoration, umbul-umbul, kober and other ceremony facilities for decoration in daily businesses, mis management of Nyepi package, inapropriate management of pura hotel, etc.